(untitled) (Research, Society and Development, 2020)
Enteral nutritional therapy (ENT) is of great importance in the recovery of patients in critical condition, needing to maintain nutritional and microbiological quality to meet the needs of the patient. The present study has a theme related to the hygienic-sanitary situation, and aims to conduct a literary review of good practices in enteral diets, relating them to the contamination that can occur in a hospital environment. Data collection was carried out at the Virtual Health Library (VHL) and Google Scholar using the following descriptors: enteral nutrition, good practices, food and nutritional security and quality control. For the sample, the inclusion criteria were articles published from 2013 to 2020, national or international with full text in English, Spanish or Portuguese. Of the 33 articles found, 7 were used for analysis, interpretation and discussion. It was observed in the studies analyzed a relationship between the contamination of the diets with the handler and the medium in which the food is prepared, making it necessary to carry out periodic training with the team that handles the enteral diets in order to encourage daily practice good practices in the work environment as well as personal hygiene, offering a diet without microbiological risks, an important fact in the recovery of the patient and the presence of the responsible technician is also essential.